2018
DOI: 10.3390/molecules23061270
|View full text |Cite
|
Sign up to set email alerts
|

An Electron-Transporting Thiazole-Based Polymer Synthesized Through Direct (Hetero)Arylation Polymerization

Abstract: In this work, a new n-type polymer based on a thiazole-diketopyrrolopyrrole unit has been synthesized through direct (hetero)arylation polycondensation. The molar mass has been optimized by systematic variation of the the monomer concentration. Optical and electrochemical properties have been studied. They clearly suggested that this polymer possess a high electron affinity together with a very interesting absorption band, making it a good non-fullerene acceptor candidate. As a consequence, its charge transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(37 reference statements)
4
1
0
Order By: Relevance
“…284 and 7 are both PUs with thiazole structures. This result is in agreement with previous work, which suggest that the low reorganization energy of thiazole can promote the hopping of electrons between units in OSC molecules, and the electron affinity of thiazole units is always higher than 3 eV and can reduce the barrier of electron injection. PU No. 423 is a BTI structure and is an effective acceptor PU in n-type OSCs.…”
Section: Resultssupporting
confidence: 93%
“…284 and 7 are both PUs with thiazole structures. This result is in agreement with previous work, which suggest that the low reorganization energy of thiazole can promote the hopping of electrons between units in OSC molecules, and the electron affinity of thiazole units is always higher than 3 eV and can reduce the barrier of electron injection. PU No. 423 is a BTI structure and is an effective acceptor PU in n-type OSCs.…”
Section: Resultssupporting
confidence: 93%
“…7 are both polymer units with thiazole structures. This result is in agreement with the results in previous work, in which the low reorganization energy of thiazole can promote the hopping of electrons between units in OSC molecules 53 , and the electron a nity of thiazole units is always higher than 3 eV and can reduce the barrier for electron injection [72][73][74][75] . Polymer unit No.…”
Section: Identi Cation Of Key Polymer Units That Greatly In Uence Osc...supporting
confidence: 93%
“…Since 10 mol % TMEDA resulted in the highest M n among the different TMEDA concentrations studied, increasing the monomer concentration with respect to IDT was an additional parameter varied to obtain higher M n . Previous studies have investigated the effects of M n as a function of monomer concentration and observed that high monomer concentrations led to higher M n . These results corroborate with kinetic experiments performed by Fagnou and co-workers, concluding the first-order dependency of the C–H monomer concentration in the direct arylation mechanism . For our p­(IDT–TIT) system, there was a slight increase in crude (i.e., before Soxhlet) M n from 13.9 to 15.2 kg/mol when the monomer concentration increased from 0.05 to 0.09 M, respectively; however, the M n isolated from the hexane fraction remained similar (Table , entries 3 and 6).…”
Section: Introductionsupporting
confidence: 90%